MOBILE-ASSISTED LANGUAGE LEARNING IN A UNIVERSITY CONTEXT IN VIETNAM: STUDENTS’ ATTITUDES - Tra, Pham Thu (VNU Journal of Foreign Studies; Vol 36 No 1DO - 10.25073/2525-2445/vnufs.4502, 2020)
The study concerns the attitudes towards Mobile-assisted language learning (MALL) of the participants in a university. Using the mixed-method research design with survey questionnaire as the main data collection tool, the research gained some significant findings and successfully met the aims of the study. The findings from both qualitative and quantitative data reveal that the participants basically held positive attitudes towards the use of MALL inside classroom and towards MALL in general. It is suggested that MALL be adopted as a new approach in English language teaching and learning. Moreover, some measures should be taken to develop the digital literacy of both instructors and learners.